The HR value proposition - Ulrich, David, 1953-; Brockbank, Wayne (Boston, Mass. : Harvard Business School Press, 2005)
"The international bestseller Human Resource Champions helped HR professionals become more strategic players in their organizations. Now, as transactional activities like payroll and benefits administration are being increasingly automated and outsourced, the time is ripe for HR professionals to validate - and expand - this strategic role." "To make this happen, HR thought leaders Dave Ulrich and Wayne Brockbank argue that HR professionals must evaluate their value as created in the eyes of stakeholders - customers and investors as well as managers and employees. They must focus less on what they do and more on what they deliver. And they must build value-added HR practices and competencies that align with and help accomplish strategic goals." "The HR Value Proposition offers an actionable blueprint for how HR can make this transformation. Drawing on an eighteen-year global study of more than twenty-nine thousand HR professionals and line managers, Ulrich and Brockbank identify the fourteen HR criteria that have the greatest impact on value creation and outline what HR must do to build them."--BOOK JACKET.
The premise of HR value -- External business realities -- External stakeholders : investors and customers -- Internal stakeholders : line managers and employees -- HR practices that add value : flow of people and performance -- HR practices that add value : flow of information and work -- Building an HR strategy -- HR organization -- Roles for HR professionals -- HR competencies that make a difference -- Developing HR professionals -- Implications for the transformation of HR.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Personnel departments; Personnel management; Personeelsmanagement; Personnel, Services du -- Guides, manuels, etc; Personnel -- Direction -- Guides, manuels, etc; Personnel -- Direction; Personnel departments; Personnel management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books